Psychiatric symptoms and the association with parents' psychiatric symptoms among recently arrived asylum-seeking children in Finland - Parviainen Heidi; Kiviruusu Olli; Lämsä Riikka; Skogberg Natalia; Castaneda Anu E; Santalahti Päivi (SPRINGER, 2022)
This study examined psychiatric symptoms and the association with parents’ psychiatric symptoms among recently arrived accompanied asylum-seeking children in the age groups of 2–6 years (n = 93) and 7–12 years (n = 91). Children and parents were assessed using mental health and trauma measures (SDQ, HSCL-25 and PROTECT). The prevalence of total difficulties was 34.9% among 2–6-year-olds and 29.6% among 7–12-year-olds. The most common symptoms in both age groups were peer problems, followed by conduct problems among 2–6-year-olds and emotional symptoms among 7–12-year-olds. In both age groups, the children’s emotional symptoms were associated with the parents’ anxiety and depression as well as the trauma symptoms, while the conduct problems were only associated with the parents’ trauma symptoms. In conclusion, peer problems as well as conduct problems and emotional symptoms are common among recently arrived asylum-seeking children. To support the mental health of these children, both children and parents need adequate support.